The “Cultural Landscape” of Australia in Bush Ballads: Slim Dusty’s Aussie Sing Song - Krzysztof Kosecki (Anglica. An International Journal of English Studies)
The concept of the “cultural landscape” designates tangible and intangible elements of human activity, such as the natural environment, material culture, values, behaviours, and language (Taylor 2008, 6; Taylor and Lennon 2011, 538–540; Wierzbicka 1997, 201). These themes are all present in Australian bush ballads – a literary and folk genre that reflects the country’s unique heritage and way of life in simple artistic forms. Slim Dusty’s Aussie Sing Song (1962) – a representative selection of ballads – depicts Australia’s fauna and flora, the Aborigines, the beginnings of European settlement, the economy, the Great Outback, and the social role of drinking beer. The popular texts contain condensed and vivid images of the country’s culture.